Examining the role of digitalization and gig economy in achieving a low carbon society: an empirical study across nations - Liu, Kai; Feng, Zerong; Zhang, Qihang (Frontiers in Environmental Science, 2023)
Introduction: This paper investigates the international relationship between digitalization, the gig economy, and low carbon development, providing valuable insights for governments and stakeholders seeking to advance sustainable development and a low-carbon society. Methods: A large dataset comprising countries with varying degrees of digitalization and gig economy prevalence was analyzed to assess the impact of digitalization on the gig economy and its subsequent effects on greenhouse gas emissions. Results: The study reveals that the impact of digitalization on the gig economy varies by income level, exhibiting a positive relationship in high-income countries and a negative relationship in low-income countries. Furthermore, the gig economy demonstrates a significant negative impact on greenhouse gas emissions, particularly CO2 emissions, indicating that its growth may support emissions reduction and facilitate the transition to a low-carbon society. The gig economy also mediates the connection between digitalization and low-carbon development. Discussion: These findings carry substantial policy implications for governments and stakeholders working towards sustainable development and a low-carbon society. Moreover, the study highlights potential areas for future research, such as investigating the heterogeneous effects across income levels, exploring sectoral differences in the gig economy, and examining the dynamic nature of the gig economy and digitalization.